METHODOLOGY FOR THE FORMATION OF COMPETENCES OF FIRST DEGREE HOLDERS IN THE DISCIPLINE «MATHEMATICAL FOUNDATION OF INFORMATION SECURITY» - Пахомова, Вікторія (Modern engineering and innovative technologies, 2023)
The proposed methodology "MathFISLearn" for the formation of competencies of applicants for the degree "bachelor" in distance learning in the discipline "Mathematical foundations of information security": 1) the study of basic mathematical concepts, theo